2020
DOI: 10.1002/ange.201913058
|View full text |Cite
|
Sign up to set email alerts
|

Excited‐State Aromaticity of Gold(III) Hexaphyrins and Metalation Effect Investigated by Time‐Resolved Electronic and Vibrational Spectroscopy

Abstract: Expanded porphyrins with appropriate metalation provide an excellent opportunity to study excited‐state aromaticity. The coordinated metal allows the excited‐state aromaticity in the triplet state to be detected through the heavy‐atom effect, but other metalation effects on the excited‐state aromaticity were ambiguous. Herein, the excited‐state aromaticity of gold(III) hexaphyrins through the relaxation dynamics was revealed via electronic and vibrational spectroscopy. The SQ states of gold [26]‐ and [28]‐hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…19,73 Furthermore, direct observation of Baird (anti)aromaticity by time-resolved IR spectroscopy in expanded porphyrins revealed that an aromaticity reversal and associated structural changes are completed within the time resolution of the measurements, 200−300 fs. 74,75 In this regard, the results of our simulations provide not only temporal information on the reversal of aromaticity but also an important insight into its applicability to excited-state photochemistry.…”
Section: Resultsmentioning
confidence: 93%
“…19,73 Furthermore, direct observation of Baird (anti)aromaticity by time-resolved IR spectroscopy in expanded porphyrins revealed that an aromaticity reversal and associated structural changes are completed within the time resolution of the measurements, 200−300 fs. 74,75 In this regard, the results of our simulations provide not only temporal information on the reversal of aromaticity but also an important insight into its applicability to excited-state photochemistry.…”
Section: Resultsmentioning
confidence: 93%